Assessment of pain in patients with juvenile rheumatoid arthritis: relation between pain intensity and degree of joint inflammation. - Ilowite, N T (1992)
The relation between pain and joint inflammation in patients with juvenile rheumatoid arthritis has not previously been systematically evaluated. Eighteen patients with juvenile rheumatoid arthritis completed paediatric pain questionnaires and the joints affected were examined by thermography. Although significant correlations were shown between parent and doctor pain intensity ratings and joint temperature, correlations of patient pain intensity ratings and joint temperature were only significant in younger children. The degree of joint inflammation is only one factor of several contributing to the amount of subjective pain experienced by children with juvenile rheumatoid arthritis, indicating the need for a comprehensive assessment of the relatively independent variables of inflammation and pain in children with juvenile rheumatoid arthritis.